Mechanical behaviour of sisal palm glass fiber reinforced composite with addition of nano silica. (2021) - Raghul, K.S.; Logesh, M.; Kiran Kisshore, R.; Muhila Ramanan, P.; Muralitharan, G.
Abstract: In recent years, great attention is showed towards the development of reinforced composite fiber. Reinforced composite fibers replace glass and carbon fiber because it exhibits better mechanical properties such as stiffness, impact strength, flexibility and modulus. Poor resistance to moisture and its forms aggregate during processing make it more difficult to use them in a certain application. Several treatments and modifications have been done to remove moisture content and increase the cellulose content such as alkali treatment using 10%NaOH for 2hr. In this present work, we are investigating the effect of the addition of silica nanoparticle content in the sisal-palm-glass fiber-reinforced composite fabricated via hand lay-up followed by hot press molding and their mechanical behaviour like tensile strength, flexural strength and impact strength are evaluated. The results showed that maximum tensile and flexural strength are achieved when 2% Nano-silica added to the sisal-palm-glass fiber and the result shows that the incorporation of 1% of Nano-silica has significant effects on the Charpy impact behaviour.